Shape and Spreading of Platelets from the Blood of Patients with Acute Myocardial Infarction - Vasilieva, E J; Orlov, V N; Barkagan, Z S (Thrombosis and Haemostasis, 1984)
The shape of platelets in circulating blood and alterations of this shape after the contact of platelets with glass surfaces, as well as spontaneous platelet aggregation, were examined in patients with acute myocardial infarction (AMI) and in controls.The shape of circulating platelets were studied by scanning electron microscopy and the spreading - by differential interference contrast microscopy.Most platelets circulating in the blood of the patients with AMI had non-activated discoid shape; the percentage of these nonactivated platelets was similar to that in the control group. However, these platelets of many AMI patients acquired an increased ability to undergo morphological changes after contact with glass. The percentage of spread platelets in controls was never higher than 50%. In contrast, this percent was higher than 50% in 73% of patients with AMI. Increased spontaneous platelet aggregation was determined only in 30% of AMI patients.
Keywords: Platelets; DIC microscopy; SEM microscopy; Myocardial infarction